2016
DOI: 10.9758/cpn.2016.14.3.286
|View full text |Cite
|
Sign up to set email alerts
|

A Questionnaire-based Study of the Views of Schizophrenia Patients and Psychiatric Healthcare Professionals in Japan about the Side Effects of Clozapine

Abstract: ObjectiveIt is well documented that clozapine treatment causes agranulocytosis, but it can also induce drowsiness, constipation, and hypersalivation; however, these symptoms are usually less severe. It has been reported that clozapine-treated patients with schizophrenia and psychiatric healthcare professionals consider different side effects to be important. The aim of this study was to assess current practice related to the side effects of clozapine in clozapine-treated patients with schizophrenia and psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…In this study, the population of patients was a similar size to clozapine-related studies reported in the literature. In addition, this study group had similar characteristics to those in other related studies [ 2 , 5 , 10 , 21 , 22 , 23 ]. There were more males than females, with a mean age of 44 years, taking a mean dose of 350 (±136) mg of clozapine per day.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this study, the population of patients was a similar size to clozapine-related studies reported in the literature. In addition, this study group had similar characteristics to those in other related studies [ 2 , 5 , 10 , 21 , 22 , 23 ]. There were more males than females, with a mean age of 44 years, taking a mean dose of 350 (±136) mg of clozapine per day.…”
Section: Discussionsupporting
confidence: 53%
“…Whilst clozapine-induced agranulocytosis is the main fear with treatment, and is the main reason for intensive monitoring, recent evidence from pharmacovigilance databases suggests that GI complications (constipation, intestinal obstruction and paralytic ileus) are the leading cause of clozapine-related deaths [ 32 ]. Clozapine-induced constipation ranges from 14% to 60% [ 23 , 33 ]. In this study, over a fifth of the population suffered with constipation (21.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting with the limited literature on knowledge about clozapine, several studies investigated users' attitudes towards the benefits and risks of clozapine treatment. The positive view of most users about its benefits and advantages compared with prior antipsychotics is a consistent finding across surveys (31)(32)(34)(35)37,41,43,45). Comparable attitudes were found in relatives of clozapine users (34,36).…”
Section: Studies On Educational Needsmentioning
confidence: 68%
“…The characteristics of the studies are described in Table 1. Most studies were carried out in psychiatric hospitals (n = 9) (25,(32)(33)(34)(35)(36)(37)(38)(39). Other mental health settings were community mental health structures (n = 4) (40-43) and clozapine out-patient clinics (n = 3) (26,31,44).…”
Section: Studies On Educational Needsmentioning
confidence: 99%
See 1 more Smart Citation